(untitled) (Al-Qamar, 2021)
Islam is a complete and comprehensive code of life. Islam has far-reaching and result-oriented instructions to deal with our fellow Muslims in the most upright and beautiful manners. Human beings can seek guidance that enables them to deal/treat the non-Muslims in an excellent way on the basis of justice and equality. Dr. Muhammad Sa’eed Ramadan Al-Buti was a great scholar of his time. He wrote numerous books on different subjects with valuable ideas and perspectives. In this article, his analytical study about Islamic etiquettes of dealing with the Non-Muslims will be presented. Dr. Al-Buti viewed friendship and overly-compassionate behavior towards the Non-Muslim to be Haram (Impermissible) as numerous Holy Verses of the Glorious Quran that indicate on the impermissibility of establishing friendship with the Non-Muslims. However, the impermissibility of being fraternizing with them does not necessitate the impermissibility about them to be treated with tolerance and forbearance. In fact, justice highlights that they should be treated with kindness and soft speech. Neither does it necessitate that the Non-Muslims should be oppressed nor does emphasizes that they should be deemed in society as despicable people and to be treated in such a way. The Holy Prophet Muhammad’s (ﷺ) blessed autobiography teaches the humanity to treat them without any discrimination. They must be treated politely and graciously with tolerance and good etiquettes.